A full thermal model for photovoltaic devices. (15th December 2016) - Dupré, Olivier; Vaillon, Rodolphe; Green, Martin A.
Graphical abstract: Highlights: A model of the heat sources and the temperature is established for photovoltaic devices. The dependence of the heat source on the applied bias suggests redefining the NOCT. A thermal modeling is key to maximizing conversion efficiency in real operating conditions. Abstract: A full thermal model for photovoltaic devices is presented. It consists of describing the physics of the conversion losses that come with heat dissipation together with giving analytical expressions of the associated heat sources. The consistency of the model is demonstrated by its application to a crystalline silicon solar cell. The modeling is completed by the balance equation which drives the equilibrium temperature of the cell. The impact of considering a full thermal model for designing photovoltaic devices is illustrated with two examples related to solar cells. First, the dependence of the heat source on the applied bias suggests that the Nominal Operating Cell Temperature should be defined at the Maximum Power Point instead of at open circuit and also could be function of representative climate conditions and mounting configurations. Second, a simple combined analysis of the heat source and the dependence of output electrical power with temperature – i.e. temperature coefficient – suggests that taking into consideration a full thermal modeling of solar cells has an impact on choosing the semiconductor material that maximizes the efficiency in real operating conditions.